Z-scheme polyimide/tungsten trioxide aerogel photocatalyst for enhanced photocatalytic CO2 reduction under visible light. (14th May 2021) - Zhao, Xinfu; Yi, Xibin; Zhang, Jing; Liu, Benxue; Yu, Shimo; Liu, Xiaochan
Abstract: Developing highly efficient and stable photocatalysts is an effective method to achieve CO2 photocatalytic reduction. Herein, PI/WO3 aerogel photocatalyst was prepared by chemical amide reaction coupled with an ethanol supercritical drying technique. The novel aerogel photocatalysts exhibit excellent photocatalytic performance for reducing CO2 into CO. In particular, PI/WO3 -10 aerogel photocatalyst shows the highest yield of CO (5.72 μ mol g –1 h –1 ), which is ca 11-fold higher than that of the pristine PI aerogel. The high CO2 reduction activity can be attributed to the Z-scheme structure, which enhances the separation of photo-generated electron– holes, and induces H2 O oxidation on WO3 nanosheets and CO2 reduction on PI aerogel. The photocatalytic reaction mechanism of CO2 when using PI/WO3 aerogel photocatalyst is proposed.